Sm-Nd AND Rb-Sr ISOCHRON AGES FOR META-TRONDHJEMITES FROM CAPE HINODE, EAST ANTARCTICA - シライシ, カズユキ; カガミ, ヒロオ; ヤナイ, ケイゾウ; SHIRAISHI, Kazuyuki; KAGAMI, Hiroo; YANAI, Keizo (National Institute of Polar Research, 1995)
P(論文) A Rb-Sr and Sm-Nd isotope study of meta-trondhjemites and a pelitic gneiss from Cape Hinode, Lutzow-Holm Complex (LHC), East Antarctica has been performed. A Sm-Nd whole rock isochron for nine meta-trondhjemites defines an age of 1031±69Ma with an initial ^<143>Nd/^<144>Nd ratio of 0.5115520±0.000053 (MSWD=0.10,ε_<Nd>=+4.7±1.0). In the Rb-Sr isochron diagram, the same nine samples yield an age of 1273±104Ma with an initial ^<87>Sr/^<86>Sr ratio of 0.70275±0.00017 (MSWD=7.4) although the data are slightly scattered. The Sm-Nd isochron age is indistinguishable from the previously reported U-Pb SHRIMP zircon age (1017±13Ma). Nd model ages (T_<DM>) of the metatrondhjemites and a pelitic gneiss are ∿1.2-1.5Ga and 2Ga, respectively. Taking into account the initial ratios and the previous zircon study, we conclude that the ∿1000Ma age indicates the time of igneous crystallization of the trondhjemite. The pelitic gneiss, which probably originated from middle Proterozoic supracrustal material, is the host rock of the trondhjemite intrusion. However, the ∿500Ma high grade metamorphic age, which is ubiquitous in the LHC, is not documented in these rocks. Slight scattering in the Rb-Sr and Sm-Nd isochron diagrams might be the effect of the ∿500Ma metamorphism, but resetting of the isotopes was not complete, probably because of the scale of the 4km×5km sample collection area. departmental bulletin paper